Dispersão acionária e controle minoritário no mercado de capitais brasileiro - Alberto de Campos Cordeiro Neto (2014)
The objective of this work is the study of the phenomenon of dispersed ownership and minority control in the Brazilian capital markets, based on the exercise of control in publicly-held companies. Brazil is famously known for being a country with concentrated ownership and family-owned companies, in which the majority shareholder, who owns more than half of the voting shares, elects the majority of the companys directors and officers, directs the corporate activities and guides the operation of the companys departments. However, after the creation of Novo Mercado in 2000, Brazil initiated a process of ownership dispersion in publicly-held companies, which has been changing the consolidated scenario of the Brazilian capital markets. As a result, the minority control, exercised by a shareholder or group of shareholders who own less than half of the voting shares, gained importance in the corporate scenario. The minority control is only possible when the level of ownership dispersion is not high enough to completely dissociate ownership and control, as it seems to be the case in the Brazilian capital markets. The minority control is positioned in-between a scenario of concentrated ownership, characterized by the majority shareholder, and a scenario of highly dispersed ownership, characterized by the transfer of the companys control from the hands of the shareholders to the directors and officers (management control). When discussing the minority control, this work does not seek to analyze all the consequences of the presence of a controlling minority shareholder for the Brazilian Corporate Law, but rather discuss the categorization, the legal discipline of the minority control and its manifestation in the Brazilian law, in light of shareholder activism and public proxy solicitations.